Evaluation of heat transfer at the cavity-polymer interface in microinjection moulding based on experimental and simulation study. (5th February 2018) - Babenko, Maksims; Sweeney, John; Petkov, Petko; Lacan, Franck; Bigot, Samuel; Whiteside, Ben
Highlights: High speed IR camera used to measure melt cooling during the micromoulding cycle. Effects of surface topography on cooling through laser machined sapphire windows analysed. Experimental and simulation data compared to determine HTC value. Higher value of HTC improves cooling prediction for microinjection moulding. Abstract: In polymer melt processing, the heat transfer coefficient (HTC) determines the heat flux across the interface of the polymer melt and the mould wall. The HTC is a dominant parameter in cooling simulations especially for microinjection moulding, where the high surface to volume ratio of the part results in very rapid cooling. Moreover, the cooling rate can have a significant influence on internal structure, morphology and resulting physical properties. HTC values are therefore important and yet are not well quantified. To measure HTC in micromoulding, we have developed an experimental setup consisting of a special mould, and an ultra-high speed thermal camera in combination with a range of windows. The windows were laser machined on their inside surfaces to produce a range of surface topographies. Cooling curves were obtained for two materials at different processing conditions, the processing variables explored being melt and mould temperature, injection speed, packing pressure and surface topography. The finite element package Moldflow was used to simulate the experiments and to find the HTC values that best fitted the cooling curves, so that HTC is known as a function of the process variables explored. These results are presented and statistically analysed. An increase in HTC from the standard value of 2500 W/m 2 C to values in the region 7700 W/m 2 C was required to accurately model the observations.